Fanaticism Jacquerie, Movement, Party: Ratchet Politics and Peasant Mobililization in South India, 1836-1956 - Ron Herring
The anomalous peasant mobilization of Kerala is rooted in especially extensive structural transformations congruent with Polanyi's notion of a "great transformation" and organizational development centered on ratcheted episodes of reforms in landed and other social relations in response. The culmination was appropriation of rentier property (almost half the land in the state) and the end of agrestic slavery and serfdom. Pre-political responses to structural dislocation expressed moral outrage resulting in self-consciously suicidal confrontations with the colonial state. Inheritors of the agrarian radicalism tradition introduced organizational and tactical innovations which more effectively confronted a state traumatized by "fanatical outrages." Activists on the left understood, as academics often do not, that there is no such thing as a peasantry; creating an effective political aggregation of individuals from agrarian classes with objectively opposed interests and multiple identities requires political theory which integrates structure and agency. As a group, the "peasantry" had divergent interests which had to be submerged to effect collective action; the integrating goal evolved into the abolition of landlordism, playing on the most important structural feature of landlordism - the rent fund. Presentation of landlordism as a social system permitted a tactical integration of grievances across the spectrum of lived experience in the villages. Disappearance of the rent fund through appropriation by former tenants in the 1970s ruptured the agrarian coalition, underlining the importance of this particular structural fact to the historical aggregation process. Analytical unities across these quite different episodes of social action suggest the utility, and limits, of a collective action frame based on methodological individualism.